2023
DOI: 10.1038/s41598-023-30077-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of one million COVID-19 deaths in America: economic and life expectancy losses

Abstract: Between February 2020 and May 2022, one million Americans have died of COVID-19. To determine the contribution of those deaths to all-cause mortality in terms of life expectancy reductions and the resulting economic welfare losses, we calculated their combined impact on national income growth and the added value of lives lost. We estimated that US life expectancy at birth dropped by 3.08 years due to the million COVID-19 deaths. Economic welfare losses estimated in terms of national income growth supplemented … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…This result well matched the reality that the global economy suffered a significant negative decline during 2020 and 2021. In terms of work by Silva et al [ 43 ], the U.S. life expectancy at birth dropped by 3.08 years due to the million COVID-19 deaths. Economic welfare losses were estimated to be USD 3.57 trillion.…”
Section: Resultsmentioning
confidence: 99%
“…This result well matched the reality that the global economy suffered a significant negative decline during 2020 and 2021. In terms of work by Silva et al [ 43 ], the U.S. life expectancy at birth dropped by 3.08 years due to the million COVID-19 deaths. Economic welfare losses were estimated to be USD 3.57 trillion.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study conducted by the Advanced Highway Maintenance and Construction Technology (AHMCT) Research Center [20] reported that the average fatal accident rate in California during maintenance activities from 1972 to 2013 was 2.18×10 -7 deaths per person-hour of work on the road [21]. To compute the cost of worker fatality as a result of a car collision into the work zone, we used the most recent Valuation of a Statistical Life (VSL) published by the U.S. Department of Transportation [22,23], which reports the VSL using the base year of 2022 as equal to $12.5 million [22]. Employing the VSL and average fatal accidents, we computed the cost of workers' fatality resulting from a car collision into the work zone to be equal to $2.57 per person-hour of work.…”
Section: Workers' Fatalitymentioning
confidence: 99%
“…The COVID-19 pandemic, caused by the severe acute respiratory syndrome-related coronavirus 2 (SARS-COV-2), is responsible for a vast amount of deaths and economic disruption across the globe . Despite the development and approval of vaccines, and the antiviral drug Paxlovid, which targets the SARS-COV-2 virus, COVID-19 continues to spread and remains a severe health risk, particularly for people with underlying conditions .…”
Section: Introductionmentioning
confidence: 99%